Jelajah Habitat Binatang Virtual Berbasis Augmented Reality dengan Metode Markerless: Animal Habitats Augmented Reality-Based Virtual Roaming with Markerless Method - Muhammad Malik Ibrahim; Ayung Candra Padmasari (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Augmented Reality-based applications usually use markers as markers to store objects. However, there is a cutting-edge technology called markerless which is new in the world of Augmented Reality. This study uses SLDC with the waterfall method. As a result, making Augmented Reality-based applications using Adobe Illustrator, Blender, Unity and Vuforia applications. In addition, this application is very efficient and makes it easy for users to enjoy the view of the virtual world and the real world at the same time. Keywords—3-5keywords, Augmented Reality, Education Application, Android